Avalia??o do Servi?o de Atendimento M?vel de Urg?ncia (SAMU - 192) em Feira de Santana ? Ba: estrutura, processo e resultado - Silva, Maiza Sandra Ribeiro Macedo (2009)
The expansion of the population's access to emergency services, mainly from the construction of the National Policy for the Emergency Services (PNAU) and deployment of Mobile Service, Emergency (SAMU 192), as the main component of this policy and the strengthening of the SUS , demanded changes in the organization of network services, so as to increase the coverage of the health units in the pre-hospital fixed, as the deployment of new Service Ready (PA) to minimize the empty ports of entry in care of emergencies. The presence of SAMU component of this policy and as part of the network of services contributes significantly to the operationalization of the principles of the SUS, starting with the expansion and strengthening of access through the 192, which at that time deconstructs the geographic and economic barriers. Then there is a classification of risks, which seeks to better meet the needs of the user, at that time strengthening the principles of fairness and resolution. After that, heading up the mobile teams to the site of the emergency, which begins to approach the victim on the spot. At that time, strengthened the principles of resolution and completeness of the shares, the victim is removed and referenced to a fixed unit, which is the working principle of the entire service. This study aimed to evaluate the implementation of the SAMU - 192 in Feira de Santana-BA, the suitability of the Service PNAU, describe its structure to meet local demand, and characterize the actions of the Service in relation to the structure, processes and outcomes, using indicators adapted from PNAU. This is an evaluative research, done by the evaluation model that integrates quantitative and qualitative approaches in an attempt to bring the proposed assessment by triangulation methods. In the quantitative phase of the study was car?ter census (n = 77,593 visits), which were all attending the SAMU, the physical part, from three elements: the Emergency Regulation Center (RAW), continuing education for professionals in the SAMU, and prehospital care in the local scene, which were evaluated for the structure. The procedures and results were evaluated through a qualitative approach, using the techniques of systematic observation and documentary analysis. Through analysis, found that there was an absolute variation in the year 2007 to 2008 of -31.45% refers to the total called SAMU; trotes for the change was -59.42%, on the origin of service, the absolute variation of the so-called primary was -35.30%, while known side of +208.97%, detected the existence of continuous training, as well as the use of technical protocols for operation of the routines and care for victims ; identified is not the investment of resources in federal and state level for training of personnel, as well as number of units of basic and advanced support incompatible with the local demand. It is found that the limits are capable of resolution, depending on the partnership of the three spheres of government, and there are many prospects for advancement, which contributes to the strengthening and qualification of shares of SAMU, the PNAU and the SUS.